Krisis identitas linguistik: Eksistensi bahasa ibu di persimpangan generasi kekinian Desa Karangwuni - Utami, Ekgoan Susanti; Suryadi, Muhammad (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Weak inheritance of local languages within the family domain leads to language shift. Consequently, the phenomena of code-mixing and code-switching among children and grandchildren exhibit inconsistent and random patterns. This study aims to determine the status of local languages and identify the causes of language shift within the family environment, focusing specifically on the shift from Javanese to Indonesian. The subjects of this study consist of three generations: (1) generation 1 includes grandparents, (2) generation 2 includes parents, and (3) generation 3 includes children or grandchildren. A descriptive qualitative method was employed, utilizing interview, observation, and note-taking techniques. The results indicate a significant shift from Javanese to Indonesian. For instance, when generation 2 addresses generation 3 in Javanese, generation 3 responds in Indonesian due to a lack of Javanese vocabulary. Generation 3 only masters simple Javanese terms, such as mpun, dereng, and wonten. This phenomenon is driven by education levels, economic status, social mobility, language attitudes, and the influence of technology and social media. The shift is further evidenced by the emergence of random code-switching and code-mixing in daily family conversations.